2017
DOI: 10.1016/j.sbi.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Structural Biology outside the box — inside the cell

Abstract: Recent developments in cellular cryo-electron tomography, in-cell single-molecule Förster resonance energy transfer-spectroscopy, nuclear magnetic resonance-spectroscopy and electron paramagnetic resonance-spectroscopy delivered unprecedented insights into the inner workings of cells. Here, we review complementary aspects of these methods and provide an outlook toward joint applications in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 102 publications
0
67
0
Order By: Relevance
“…These large-scale quantitative annotations will help understand the biological role of order and disorder, and serve as a basis to construct predictive models. As NMR measurements of proteins in their native complex environments, such as inside living cells, are becoming more common ( 59 ), we will be able to address fundamental biological questions with greater physiological relevance ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…These large-scale quantitative annotations will help understand the biological role of order and disorder, and serve as a basis to construct predictive models. As NMR measurements of proteins in their native complex environments, such as inside living cells, are becoming more common ( 59 ), we will be able to address fundamental biological questions with greater physiological relevance ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…As they are involved in essentially all major human diseases, they also represent promising novel targets for drug discovery 4,5 . Experimental methods to characterize IDPs and IDRs include X-ray crystallography, nuclear magnetic resonance spectroscopy (NMR), small-angle X-ray scattering (SAXS), circular dichroism (CD) and Förster resonance energy transfer (FRET) [6][7][8][9] . Each technique provides a unique point of view on the phenomenon of intrinsic disorder (ID) and multiple experimental evidence gives researchers insights over the functioning mechanisms of IDPs.…”
Section: Introductionmentioning
confidence: 99%
“…CCS acts as a metallochaperone through its N-terminal Atx1-like domain (D1) and as oxidoreductase through its C-terminal domain (D3), whereas the second, SOD-like domain (D2) is responsible for the interaction with SOD1 15 24 . Recently, the maturation steps of SOD1 have been observed in living human cells 25 through in-cell NMR 26 , 27 . It has been shown that some WT-L fALS SOD1 mutants fail to bind zinc when they are overexpressed in the human cytoplasm, and accumulate as unstructured species that may act as precursors in the pathogenic aggregation pathway 28 .…”
Section: Introductionmentioning
confidence: 99%